2005
DOI: 10.1038/sj.ijo.0803115
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adiponectin levels, body composition and obesity-related variables in Prader–Willi syndrome: comparison with obese subjects

Abstract: Background: People with obesity and/or the metabolic syndrome have an increased risk for developing diabetes and cardiovascular disease and may have low adiponectin levels. The obesity associated with Prader-Willi syndrome (PWS) would be expected to have similar complications. However, it was recently reported that, despite their adiposity, people with PWS have reduced visceral fat and are less likely to develop diabetes mellitus or the metabolic syndrome compared with people with simple obesity. Objective: To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 33 publications
7
57
2
1
Order By: Relevance
“…In another genetic syndrome with a predisposition to obesity, Prader Willi Syndrome (PWS), the association between leptin and total body fat had an increased slope in subjects with PWS compared to controls, similar to our findings in DS (22). In two other studies, however, no difference in leptin levels were observed between subjects with PWS and controls (23,24), even after adjusting for adiposity (22). Thus, there are conflicting data about PWS as a possible syndromic model of increased leptin resistance.…”
Section: Discussionsupporting
confidence: 89%
“…In another genetic syndrome with a predisposition to obesity, Prader Willi Syndrome (PWS), the association between leptin and total body fat had an increased slope in subjects with PWS compared to controls, similar to our findings in DS (22). In two other studies, however, no difference in leptin levels were observed between subjects with PWS and controls (23,24), even after adjusting for adiposity (22). Thus, there are conflicting data about PWS as a possible syndromic model of increased leptin resistance.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the two groups were also matched for central adiposity and insulin resistance without specific selection of control subjects. Although our PWS cohort might seem unusual, as a lower visceral fat mass and preserved insulin sensitivity has been reported previously (Brambilla et al, 1997, Goldstone et al, 2001, Goldstone et al, 2004, Goldstone et al, 2005, Talebizadeh and Butler, 2005, Kennedy et al, 2006, Theodoro et al, 2006, Haqq et al, 2010and Sode-Carlsen et al, 2010, other investigators recently reported similar observations to ours, i.e. obese children and adults with PWS having the same amount of visceral fat mass, the same degree of insulin resistance and a similar prevalence of metabolic syndrome compared to carefully weight-matched obese subjects Butler, 2005 andBrambilla et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…There were no significant effects (i.e., significant positive or negative correlations (data not shown) observed for genetic subtypes (15qll-q13 deletion or maternal disomy 15) and CRP concentrations which is consistent with our previous report of adiponectin levels in PWS. 29 Additionally, we saw no significant correlations between CRP levels for body mass index (BMI), percentage of fat, weight, age, or waist to hip ratios (see Table 2). …”
Section: Resultsmentioning
confidence: 98%
“…In addition, there are only scattered reports of cerebrovascular accidents in the PWS population including a report of a teenager with PWS and type 2 diabetes mellitus and a vaso-occlusive stroke with revascularization of the middle cerebral arteries. 22 Since ischemic vascular disease is commonly linked to obesity in the general population, [23][24][25] the low number of reports or prevalence of these conditions in PWS is surprising and may be due to underreporting or perhaps to lower than expected occurrence of dyslipidemia and insulin-resistance, 26,27 higher adiponectin levels, 28,29 or lower CRP levels than commonly seen in the general obese population.…”
mentioning
confidence: 99%